Influence of buccal corridor dimension on smile esthetics - Nascimento, Diana Cunha; Santos, Êmeli Rodrigues dos; Machado, Andre Wilson Lima [UNESP]; Bittencourt, Marcos Alan Vieira (FapUNIFESP (SciELO), 2012)
Objective: To assess the influence of buccal corridor width on smile esthetics of male and female, Caucasian and Afro-descen-dant subjects by means of digitally manipulated photographs, as well as compare assessments of full-face view (FFV) and close-up view of the mouth (CUVM) images. Methods: Facial photographs were taken of four adults' smile, two Caucasians and two Afro-descendants of both genders. The resulting images were digitally manipulated with the aim of rendering - from each original smile - three other smiles simulating three different buccal corridor widths, namely, narrow, medium width and wide. The rendered images, 12 of which portraying FFVs and 12 providing CUVMs, were assessed by 60 examiners who rated the attractiveness of each smile by means of a visual analog scale (VAS). The data were treated with ANOVA and Tukey's post test to compare the different buccal corridors, and Student's t test to compare the two image views (FFV and CUVM). Results: Medium width buccal corridors were considered the most attractive in the four individuals investigated, both in the assessment of FFVs and CUVMs (p < 0. 05). Comparison between the narrow and wide buccal corridors, in general, showed no statistically significant differences (p > 0. 05). Furthermore, no statistically significant difference was found between the analyses of FFVs and CUVMs (p > 0. 05). Conclusion: The buccal corridor exercised a remarkable influence on smile esthetics, with the medium width group being rated as the most attractive. No influence was exerted by the individuals' face, ethnicity or gender. © 2012 Dental Press Journal of Orthodontics.
Keywords: Dental esthetic; Orthodontics; Smile